Effect of Sodium Alginate and Coconut Shell Liquid Smoke Concentration on The Characteristics of Restructuring Catfish (Pangasius sp.) Jerky - Ulya Sarofa; Rosida; Deane Damayanty (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Restructuring is the process of recombining crushed materials into new products with the help of binding agent. The use of sodium alginate as a binding agent and the addition of liquid smoke are expected to improve the character of catfish jerky during restructuring. The purpose of this study was to determine the effect of sodium alginate and liquid smoke addition to physical, chemical and organoleptic properties on the quality of restructuring catfish jerky. This study used a Complete Randomised Design factorial pattern with two factors: calcium alginate concentration (0,5%, 0,75%, 1%) and liquid smoke concentration (1%, 2%, 3%). The data obtained were then analysed using analysis of variance (ANOVA). If there were differences, the Duncan multiple range test (DMRT) was carried out. The research results indicate that there was an interaction between the concentrations of sodium alginate and liquid smoke, with each significantly affecting the yield, moisture content, ash content, protein content, and hardness of the restructured catfish jerky produced. Sensory evaluation showed significant effects on texture, taste, and colour parameters, but no significant effect on aroma. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 11: Sustainable Cities and CommunitiesSDG 13: Climate ActionSDG 15: Life on Land